PENGARUH MEDIA TANAM DAN MACAM BAHAN STEK TERHADAP PERTUMBUHAN Turnera subulata - Ahmad Nasir Daulay; Hangger Gahara Mawandha; Ety Rosa Setyawati (Fakultas Pertanian, Universitas Janabadra, 2023)
The research was conducted at KP2 of the Institut Pertanian Stiper located in Maguwoharjo Village, Depok District, Sleman Regency, DIY. With an elevation of 118 mpl. The research was conducted from August 4, 2022, to November 1, 2022. The research was carried out using a factorial design that was arranged in a completely randomized design (CRD) and consisted of two factors. The first factor was the planting medium, which consisted of 4 levels: M0, regosol soil (control); M1, soil + cow manure (2:1); M2, soil + rice husk (2:1); and M3, soil + cow manure + rice husk (1:1:1). The second factor is the origin of the cutting material, which consists of 3 levels, namely the top of the segment (B1), the middle stem of the segment (B2), and the rootstock ofthe segment (B3), and each is 15 cm long. So that 4 x 3 = 12 combinations are obtained. Each treatment was repeated five times, resulting in the acquisition of 60 units. Experiment The research data were analyzed by analysis of variance (Anova) at the 5% level. If there is a significant effect, a DMRT follow-up test is carried out at the 5% level. The planting medium and cutting material interacted with plant height, number of shoots, number of leaves, fresh weight of roots, and dry weight of plants. Meanwhile, for fresh weight of plants, dry weight of roots, and leaf width, there was no interaction between the planting medium and the cutting material..INTISARIPenelitian dilaksanakan di KP2 Institut Pertanian Stiper yang terletak di Desa Maguwoharjo, Kecamatan Depok, Kabupaten Sleman, DIY. Dengan ketinggian tempat 118 mpl. Penelitian dilakukan pada tanggal 04 Agustus sampai tanggal 01 november 2022. Penelitian dilakukan dengan rancangan faktorial yang disusun dalam Rancangan Acak Lengkap (RAL) dan terdiri dari dua faktor. Faktor pertama adalah media tanam yang terdiri dari 4 aras pada media tanam berupa (M0) tanah regosol (kontrol), (M1) tanah + pupuk kandang sapi(2:1) (M2) tanah + sekam padi (2:1), (M3) tanah + pupuk kandang sapi + sekam padi (1:1:1). Faktor kedua adalah asal bahan stek yang terdiri dari 3 aras yaitu bagian pucuk ruas (B1), batang tengah ruas (B2), dan batang bawah ruas (B3), dan masing masing panjang nya 15 cm, Sehingga diperoleh 4 x 3 = 12 kombinasi. Masing masing perlakuan diulang 5 kali dan didapat 60 satuan. Percobaan Data hasil penelitian dianalisis dengan analisis of variance (Anova) pada jenjang 5%. bila ada pengaruh nyata dilakukan uji lanjut DMRT pada jenjang 5%. Media tanam dan bahan stek terjadi interaksi terhadap tinggi tanaman, jumlah tunas, jumlah daun, berat segar akar, berat kering tanaman, Sedangkan di berat segar tanaman, berat kering akar, lebar daun tidak terjadi interaksi antara media tanam dan bahan stek.